Lessons learned from a muscle study in nail-patella syndrome - Paul, Luisa; Schänzer, Anne; Depienne, Christel; Hentschel, Andreas; Kohlschmidt, Nicolai; Schara-Schmidt, Ulrike; Nelke, Christopher Jannik; Roos, Andreas; Kölbel, Heike (Orphanet journal of rare diseases, 2025)
Nail-patella (NPS) syndrome is an autosomal dominant disorder caused by mutations in the LMX1B gene and manifests with involvement of kidneys, nails, eyes as well as skeletal musculature. NPS shows some clinical similarities with Emery-Dreifuss muscular dystrophy. However, thus far human muscle tissue has not been analysed in the context of NPS to precisely clarify the muscular involvement in this multi-systemic disease.
Gesehen am 11.12.2025